2021
DOI: 10.1177/17562872211007625
|View full text |Cite
|
Sign up to set email alerts
|

Urinary catheterization from 1997 to 2018: a Dutch population-based cohort

Abstract: Background: Our aim was to evaluate the use of indwelling, intermittent and external urinary catheters in neurogenic and non-neurogenic bladder patients in the Netherlands from 1997 to 2018. Methods: Data were retrieved from a population-based cohort containing information about the extramural use of medical devices in the insured population in the Netherlands. The insured population increased from 9.9 million people in 1997 to 17.1 million people in 2018 (64–100% of the Dutch population). Users are expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This is consistent with our two previous studies that evaluated the use of urinary catheters in the Netherlands with an overlapping cohort from 1997 to 2018. 11,12 They found that the number of CIC users tripled and the number of IDC users doubled over two decades. Moreover, they found an increase in CIC and IDC use in the younger age categories, which may be a result of exponential population growth, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our two previous studies that evaluated the use of urinary catheters in the Netherlands with an overlapping cohort from 1997 to 2018. 11,12 They found that the number of CIC users tripled and the number of IDC users doubled over two decades. Moreover, they found an increase in CIC and IDC use in the younger age categories, which may be a result of exponential population growth, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Extremely high in comparison to the expenditure of indwelling catheters in the Dutch outpatient setting (only 6,7 million euro for 54 000 users). 42 Almost 25% of the users had a neurogenic underlying disease, which are usually chronic users with multiple 4–6 catheterisations per day. Based on this assumption, the amount of disposable catheters used on an annual basis for users with a neurogenic underlying disease is more than 20 million disposable catheters a year.…”
Section: Discussionmentioning
confidence: 99%
“…A National Health Service England survey from across the entire system of its users found 12.9% of patients were catheterised [ 6 ]. Similarly, a Dutch survey revealed that over a 21-year period (1997–2018), indwelling catheter use per 100,000 population nearly doubled and intermittent catheter usage nearly trebled [ 7 ]. In the US, America’s Medicare & Medicaid reimburse up to 200 intermittent catheters/month/per person, encouraging single use only to minimise infections [ 8 ].…”
Section: Introductionmentioning
confidence: 99%